2023
DOI: 10.1021/acscatal.3c04509
|View full text |Cite
|
Sign up to set email alerts
|

Rational Regulation of the Exciton Effect of Acrylonitrile-Linked Covalent Organic Framework toward Boosting Visible-Light-Driven Hydrogen Evolution

Xingyue Gao,
Jiayu Yuan,
Ping Wei
et al.

Abstract: Covalent organic frameworks (COFs) exhibit relatively inefficient exciton dissociation and free charge generation, which arise from their high exciton binding energy. Here, a series of crystalline, acrylonitrile-linked COFs are fabricated to regulate exciton effects by strategies of shortening the linker length (TP-PN COF), introducing nitrogen atoms (TP-BPyN COF), and post-protonation (TP-BPyN PCOF). The temperature-dependent photoluminescence (PL) spectra and Nyquist plots reveal a decrease in exciton bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The integrated PL intensity of BTT-COFs decreased with the temperature increasing from 180 to 300 K, and the exciton binding energy ( E b ) was obtained by fitting these data based on the Arrhenius eq (Figure a, details are given in the Supporting Information). , It revealed that BTT–OH had the lowest E b (65.5 meV) compared with those of BTT–H (114.7 meV) and BTT–Me (110.3 meV), which meant the excitons were more easily dissociated into free electrons and holes in BTT–OH.…”
Section: Resultsmentioning
confidence: 97%
“…The integrated PL intensity of BTT-COFs decreased with the temperature increasing from 180 to 300 K, and the exciton binding energy ( E b ) was obtained by fitting these data based on the Arrhenius eq (Figure a, details are given in the Supporting Information). , It revealed that BTT–OH had the lowest E b (65.5 meV) compared with those of BTT–H (114.7 meV) and BTT–Me (110.3 meV), which meant the excitons were more easily dissociated into free electrons and holes in BTT–OH.…”
Section: Resultsmentioning
confidence: 97%
“…Excitons are unique electron–hole pairs produced during the photophysics process. ,, Only those excitons that are further dissociated into free charge carriers can be involved in the following photocatalytic redox reactions. However, the inherent low dielectric constants and strong Coulombic force between electrons and holes lead to large exciton binding energy, , which is unfavorable to the generation of free charge carriers in organic semiconductors .…”
Section: Strategies For Improving the Photoactivity Of Cofsmentioning
confidence: 99%
“…Another major concern is how to improve the photocatalytic performance of the COFs. In the initial steps of heterogeneous photocatalysis, a photocatalyst is excited by incident light with sufficient energy to generate excitons, that is, the bound electron–hole pairs in the crystal lattice of the photocatalyst through Coulomb interaction. , Only when the excitons are dissociated into free charge carriers (i.e., separated electrons and holes), they are available for the subsequent redox reactions; accordingly, the exciton dissociation process is crucial. It is acknowledged that the binding energy ( E b ) of exciton in a semiconductor is inversely proportional to its dielectric constant ( E b = q 2 /4πε o ε r r o , where q, ε o , ε r , and r o are the elementary charge, the absolute dielectric permittivity, the relative dielectric constant, and the distance between the electron and hole, respectively). , Inorganic photocatalysts usually hold high dielectric constants above 10 thus low exciton binding energy of 10 meV, which is equal to or less than 26 meV (i.e., the thermal disturbance energy k B T, where k B is the Boltzmann constant and T is the room temperature). , Therefore, the excitons of inorganic photocatalysts are substantially dissociated into free charge carriers. Conversely, organic photocatalysts have low dielectric constants of 3–5 and high exciton binding energy from hundreds of meV to 1 eV, thus causing large energy barriers toward exciton dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…Amazingly, the overpotential of Ru/Ru x Fe 3– x O 4 is only 17.6 mV at a current density of 10 mA cm –2 (η 10 ), lower than that of commercial Pt/C (η 10 = 30.5 mV), far better than the reported previously (Figure 14 and Table S3). , In addition, the Tafel slope for Ru/Ru x Fe 3– x O 4 is far lower than that of Pt/C, indicating the fastest reaction kinetics toward the HER (Figure S15). As shown in Figure b, the mass activity of Ru/Ru x Fe 3– x O 4 is 1576.9 mA mg Ru –1 at 50 mV, ∼10 times higher than that of commercial Pt/C (166.3 mA mg Pt –1 ).…”
mentioning
confidence: 99%